1954
DOI: 10.1099/00221287-10-2-309
|View full text |Cite
|
Sign up to set email alerts
|

The Stability of Penicillinase-producing Strains of Staphylococcus aureus

Abstract: SUMMARY : Penicillin-sensitive and penicillin-resistant colonies of Staphylococcus aureus, belonging t o the same phage pattern, were found in six out of 200 apparently resistant cultures isolated from infective processes. The in vitro instability of penicillinase-producing strains of Staph. aureus was confirmed. It was found that growth with Streptococcus haemolyticus or in the presence of other antibiotics did not greatly influence the natural development of sensitive variants. This process, however, tended … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
22
0

Year Published

1957
1957
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 6 publications
1
22
0
Order By: Relevance
“…This finding is supported by Bondi et al (1958) whose report stated that growth of S. aureus at 45°C increased the rate of loss of penicillinase production. The present finding is also consistent with the report that growth at elevated temperature (44°C) increased the rate of loss of penicillinase resistance in some strains of Staphylococci (Fairbrother et al, 1954). May et al (1964) showed that loss at both penicillin and tetracycline resistance during growth of a strain of S. aureus occurred at 43°C to 44°C.…”
supporting
confidence: 82%
See 1 more Smart Citation
“…This finding is supported by Bondi et al (1958) whose report stated that growth of S. aureus at 45°C increased the rate of loss of penicillinase production. The present finding is also consistent with the report that growth at elevated temperature (44°C) increased the rate of loss of penicillinase resistance in some strains of Staphylococci (Fairbrother et al, 1954). May et al (1964) showed that loss at both penicillin and tetracycline resistance during growth of a strain of S. aureus occurred at 43°C to 44°C.…”
supporting
confidence: 82%
“…Fairbrother et al (1954) reported that growth of some strains of Staphylococci at elevated temperature (44°C) increased the rate of loss of penicillin resistance. May et al (1964) reported loss of both penicillin and tetracycline resistance by S. aureus when grown at elevated temperature of 43 to 44°C.…”
Section: Introductionmentioning
confidence: 99%
“…They include plasmids conferring resistance to antibiotics (Fairbrother, Parker & Eaton, 1954;Novick, 1963;Chabbert, Baudens & Gerbaud, 1964;May et al 1964;Dornbusch, Hallander & Lofquist, 1969;Novick, 1969), heavy metal ions (Richmond & John, I 964; Novick I 967), toxin and pigment production (Serwin-Massieu, I 961 ; Dornbusch, Hallander & Lofquist, 1969). Some strains carry more than one plasmid and strains carrying two different penicillinase plasmids have been constructed artificially (Richmond,I 968) as have strains carrying both chromosomal and extrachromosomal genes for penicillinase production (Asheshov,I 969).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is currently accepted that the increase in the prevalence of penicillinase-producing strains is primarily the result of selection by penicillin, though phage-mediated transduction of penicillinase-producing capacity R. P. NOVICK may be a contributory factor (Ritz & Baldwin, 1961). On the other hand, it has been observed that penicillinase-positive strains give rise frequently to penicillinase-negative variants (Barber, 1949; Bondi, Kornblum & de Saint Phalle, 1953;Fairbrother, Parker & Eaton,!1954). These strains are usually stable in that, like wildtype penicillinase-negatives, they do not revert to penicillinase production (Fairbrother, 1956).…”
Section: Introductionmentioning
confidence: 99%